Respecting recovery: research relationships with people with mental illness. (10th August 2015) - Milbourn, Benjamin; McNamara, Beverley A; Buchanan, Angus J
Abstract : Purpose: – The lived experience of individuals who experience mental illness should be at the heart of recovery-orientated practice and research. The purpose of this paper is to outline key ethical and practical issues that both respect principles of recovery and are fundamental to establishing and maintaining a research relationship with people with severe mental illness (SMI). Design/methodology/approach: – Theoretical frameworks of recovery, discourse ethics and critical reflexivity were used in a 12-month longitudinal community study to construct and build methodology to inform the collection of rich descriptive data through informal discussions, observations and interviews. Detailed field notes and a reflective journal were used to enable critical reflexivity and challenge normative assumptions based on clinical and lay views of SMI. Findings: – The paper provides an analysis through three vignettes which demonstrate how the principles of recovery were incorporated in an ethically grounded research relationship. Research limitations/implications: – The study may have been limited by the small sample size of participants. Practical implications: – Aspects of the research methodology may potentially be adopted by researchers working with people who experience SMI or with other hard-to-reach groups. Originality/value: – As more research is undertaken with individuals who experience SMI, stigma around understandings of mental illness can be broken down by supporting individuals to find their voice through recovery orientated discourse ethics.